Impact of visual guidance error on automatic carrier landing performance - ZHEN Chong; QU Xiaolei; WANG Yifeng; ZHANG Yuxiang; HAN Fengming (Hangkong gongcheng jinzhan, 2025)
The positioning accuracy of guidance system is the key factor of automatic carrier landing system to determine the success or failure of the carrier landing. The airborne equipment visual guidance architecture of carrier-based aircraft is proposed，and the positioning principles，measurement errors and effects on automatic carrier landing of airborne visual guidance architecture are investigated. The coplanar P4P relative positioning issue by means of cooperative landing aids is studied. Considering F/A-18A carrier-based aircraft automatic landing task，the simulated positioning measurement accuracy of airborne visual guidance from gliding to touchdown are estimated. The disturbances of automatic carrier landing system delay，airborne sensor noises，air-wake and deck motion are introduced，the multi-factor coupled simulation system is modeled，and the touchdown position standard errors are calculated based on Monte-Carlo simulations influenced by the disturbances. The results show that the positioning accuracy and automatic landing performance of the proposed airborne visual guidance architecture can achieve the performance of traditional guidance architectures. The deck motion and air-wake play important roles in automatic carrier landing performance.